A Green Mechanochemical One-Pot Three-Component Domino Reaction Synthesis of Polysubstituted Azoloazines Containing Benzofuran Moiety: Cytotoxic Activity Against HePG2 Cell Lines. (26th May 2020) - Mokhtar, Mohamed; Saleh, Tamer S.; Ahmed, Nesreen S.; Al-Bogami, Abdullah S.
ABSTRACT: A one-pot procedure for the synthesis of azolopyrimidine derivatives by a three-component reaction of β-ketosulfone, aldehyde, and 2-aminoben-zimidazole over synthetic magadiite clay (SMC-H) under ball milling in the absence of any solvent and additive has been developed. The catalyst was re-used for consequent reactions. The novel manufactured compounds were verified for HePG2 cell development inhibition. A pronounced inhibitory effect on the growth of HePG2 cell line was recorded. This protocol offers a broad scope for an access to a variety of diversely substituted azolopyrimidines of high inhibition activity against HePG2 cell line. The use of non-hazardous organic solvent, ball milling, cost efficiency, recyclability of the catalyst up to six runs without appreciable loss of activity, and high yields of products make this procedure greener.